Exposition of the mimesis of Tragedy in Aristotle’s Poetics (6-19) - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2023)
The aim of this article is to present a new Polish translation of Aristotle’s Poetics, namely, those of its central chapters (6–19) that deal with the Stagirite’s explication of the mimesis of tragedy. When interpreting the first five chapters of the treatise, it is important to recognize the mimetic distinctions and forms according to means and objects as well as the question of how poetic creativity takes shape (generally from improvisation through epic to comedy and tragedy). On the basis of these preliminary assumptions, Aristotle proceeds to define tragedy and analyze its components, forms and functions in more detail. Unlike the previous Polish translations of the Poetics, we have attempted here to render Aristotle’s essential technical expressions as faithfully as possible, without distorting them in accord with various concepts of modern aesthetics or literary criticism. We have also sought to preserve the Stagirite’s typical composition and his complex argument. Only in this way can the sense of Aristotle’s leading assumptions and distinctions be properly discerned. For the ease of reading, we also introduce more paragraphs and relevant subject headings into the text.